2021
DOI: 10.3390/vaccines9050474
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal and Influenza Vaccination Rates and Pneumococcal Invasive Disease Rates Set Geographical and Ethnic Population Susceptibility to Serious COVID-19 Cases and Deaths

Abstract: This study examines the relationship of pneumococcal vaccination rates, influenza, measles-mumps-rubella (MMR) diphtheria-tetanus-pertussis vaccinations (DTP), polio, Haemophilus influenzae type B (Hib), and Bacillus Calmette–Guerin (tuberculosis) vaccination rates to COVID-19 case and death rates for 51 nations that have high rates of COVID-19 testing and for which nearly complete childhood, at-risk adult and elderly pneumococcal vaccination data were available. The study is unique in a large number of nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 179 publications
2
12
0
Order By: Relevance
“…The analysis of US and Italian regional data confirmed these previous results demonstrating positive correlations between IPD prevalence and COVID-19 rates, as well as negative correlation between pneumococcal vaccination and COVID-19 rates [4]. Bernstein and colleagues analysed international data on both influenza and pneumococcal vaccination rates and reported that the influenza vaccination rate in adults ≥65 years, in combination with pneumococcal vaccination rate, provided significantly higher protection against the risk of COVID-19 compared to individual vaccines [4]. Therefore, the authors hypothesized a possible protective synergism between pneumococcal and influenza vaccines in preventing the acquisition of SARS-CoV-2.…”
Section: The Impact Of Influenza and Pneumococcal Vaccinations On Covid-19 Pandemicsupporting
confidence: 84%
See 2 more Smart Citations
“…The analysis of US and Italian regional data confirmed these previous results demonstrating positive correlations between IPD prevalence and COVID-19 rates, as well as negative correlation between pneumococcal vaccination and COVID-19 rates [4]. Bernstein and colleagues analysed international data on both influenza and pneumococcal vaccination rates and reported that the influenza vaccination rate in adults ≥65 years, in combination with pneumococcal vaccination rate, provided significantly higher protection against the risk of COVID-19 compared to individual vaccines [4]. Therefore, the authors hypothesized a possible protective synergism between pneumococcal and influenza vaccines in preventing the acquisition of SARS-CoV-2.…”
Section: The Impact Of Influenza and Pneumococcal Vaccinations On Covid-19 Pandemicsupporting
confidence: 84%
“…Pneumococcal vaccination was associated to a reduction in the risk of SARS-CoV-2 infection, as well as rates of pneumococcal vaccination were reported to inversely correlate with prevalence and mortality from COVID-19 [ 24 ]. The analysis of US and Italian regional data confirmed these previous results demonstrating positive correlations between IPD prevalence and COVID-19 rates, as well as negative correlation between pneumococcal vaccination and COVID-19 rates [ 4 ]. Bernstein and colleagues analysed international data on both influenza and pneumococcal vaccination rates and reported that the influenza vaccination rate in adults ≥65 years, in combination with pneumococcal vaccination rate, provided significantly higher protection against the risk of COVID-19 compared to individual vaccines [ 4 ].…”
Section: The Impact Of Influenza and Pneumococcal Vaccinations On Covid-19 Pandemicsupporting
confidence: 80%
See 1 more Smart Citation
“…Vaccination against SARS‐CoV‐2 as well as against recognized coinfections such as Streptococci, Haemophilus , and influenza virus should decrease risk of coagulopathies by preventing bystander or complementary co‐infections, just as they decrease risk of severe COVID‐19 in general. [ 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 ] Additionally, the results reported here may provide insight into the causes of menstruation alterations reported by some women following SARS‐CoV‐2 vaccination. [ 112 ] Finally, the present work has implications for future SARS‐CoV‐2 vaccine design, implying that whole virus SARS‐CoV‐2 vaccines may present an extraordinary risk of inducing coagulopathies compared with the mRNA, peptide, or subunit vaccines because of the very large number of blood protein mimics present; however removing molecular mimicry regions from SARS‐CoV‐2 mRNAs, proteins and their virus vectors may significantly improve vaccine safety.…”
Section: Conclusion: Testing and Preventing Covid‐19 Autoimmunity And Making Vaccines Safermentioning
confidence: 84%
“…Using Google and several websites of official public health agencies across 51 nations, [57] aimed to extend a previous ecological study of the effects of vaccines on COVID-19 cases and death rates. They also tested possible additive and synergistic vaccination effects of COVID-19 prophylaxis for controlling co-variance among vaccines.…”
Section: Community Health Profilingmentioning
confidence: 99%